Technology Meets Postmodern Epistemology: The Discourse of Hebrew Wikipedia Deletion Pages - Leshnick, Anat; Livio, Oren (AoIR Selected Papers of Internet Research, 2016)
This study examines the ways in which Hebrew Wikipedia users negotiate the boundaries of what is considered to be legitimate and worthy encyclopedic knowledge on discussion pages where debates over the proposed deletion of entries are carried out. Reflecting cultural perceptions of the relation between technology and epistemology in an age characterized by an ongoing tension between modernist and postmodern conceptions of truth, knowledge, and authority, and in an arena in which older technological and economic constraints limiting the amount of information that can be published no longer apply, the discussions illustrate how Wikipedia editors nevertheless construct the site’s informational boundaries using traditional hierarchies of importance and value, as well as through appeals to the authority of traditional institutions. At the same time, however, they also often appeal to justifications such as popularity as a source of encyclopedic importance. We explore the juxtaposition of universal arguments based upon claims to Wikipedia’s global uniformity with arguments situated in local culture and meanings, and discuss the ways in which the discourse on deletion pages helps expose ongoing struggles over the meaning and status of contemporary encyclopedic information and knowledge.